Non-suicidal self-injury and impulsivity: Study of inibithory control in adolescent population. (13th April 2021) - Pacifici, S.; Baglioni, V.; Cammisa, L.; Guerrini, D.; Mancini, C.; Mirabella, G.; Terrinoni, A.
Abstract : Introduction: Non-suicidal self-injury (NSSI) is a clinical condition defined as intentional, self-inflicted act causing pain or superficial damage without suicidal intents (12-35% of the adolescent community). Several findings show a high correlation between NSSI and impairments in the impulsivity control. Objectives: The goal of our study is to evaluate the role of impulsivity in NSSI adolescents, relatively to the inhibitory control, in order to investigate if it can represent a neurocognitive risk factor underlying maladaptive behaviours and which psychopathological dimensions can be associated with this neurobiological process. Methods: 30 NNSI inpatients (age range: 12 to 18 years), drug-free, were compared with an age-matched control group, using two behavioural paradigms for the study of inhibitory control: the Stop Signal task and the emotive go/Nogo. Psychopathological traits were evaluated by self-report questionnaires for impulsivity dimensions, suicidality and self-injurious acts. Statistical analyses were performed with SPSS program (p =0.05). Results: NSSI patients did not present impairments in the global inhibitory control but they had longer movement times in both paradigms and faster reaction times in the Go/no-go behavioural paradigm. Therefore, NSSI patients tended to be impulsive at an early stage of movement (rapid TR) and have to slow down in a second phase (TM slow) in order to have time to rework the cognitive processes underlying movement. Conclusions: The impulsivity dimension is a complex construct that involves multiple interconnected factors. The study of neuro-cognitive and psychopathological aspects and how they are interconnected is necessary to draw new perspectives on the etiopathogenesis of NNSI.